Producing wood particleboards with the inclusion of polystyrene - Rodrigues, Felipe Reis [UNESP]; Cazella, Pedro Henrique da Silva [UNESP]; de Souza, Matheus Viana [UNESP]; Bispo, Rodrigo Andraus [UNESP]; Assis, Letícia Freitas [UNESP]; Gilio, Caroline Graminha [UNESP]; Christoforo, André Luis; da Silva, Sérgio Augusto Mello da [UNESP] (Universidade Federal de Santa Maria, 2023)
The growth of human consumption has caused countless inconveniences to the environment, including the inappropriate disposal of inorganic materials with a long useful life. The incorporation of potential residues in the manufacture of wood-based particleboards presents itself as an alternative to this problem. This research by objective to evaluate the effects of replacing partial of wood particles of expanded polystyrene particles bonded with mammon bean polyurethane. Wood particles (50% pine + 50% Eucalyptus) were replaced by 25 and 50% (by mass) of expanded polystyrene particles in order to improve the physical and mechanical properties of panels manufactured with 5% polyurethane adhesive based on mammon oil. Composites manufactured with 50% of polystyrene particles resulted in the best values of the evaluated physical and mechanical properties (ABNT NBR 14810 and EN 312), designating credibility to the production of panels with the partial replacement of wood particles by polystyrene particles.
Produção de painéis de partículas de madeira com inclusão de poliestireno
Keywords: Eucalyptus; Particleboard; Pine; Polystyrene; Recycling